Upaya untuk Mencegah Penyakit Diabetes pada Usia Dini - Agus Rohmat Hidayat; Hanipah Hanipah; Aisyah Nurjanah; Rafi Farizki (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Diabetes Mellitus is a metabolic disorder that arises due to an increase in blood sugar levels that are above normal values that take place chronically. Indonesia is currently the 5th country with the highest prevalence of diabetes in the world. Diabetes Mellitus is a disease that cannot be cured, but can be prevented by adopting a healthy lifestyle properly. Objective: to analyze efforts that can be made to prevent diabetes from an early age. Method: The research method used is qualitative research with data collection techniques by conducting document reviews through data collection or scientific work that aims to collect bibliographical information. The technical data analysis uses the Miles and Huberman models. Results: (1) regulate diet; (2) doing physical activity; (3) checking sugar levels periodically; and (4) involve the role of the family in the prevention of diabetes. Conclusion: Diabetes Mellitus prevention efforts must be implemented early to minimize the risks that will occur in the future.